Exploring Anxiety Levels in Mathematics and Gender Dispositions among Students in Secondary School - Onoshakpokaiye, Odiri E; Eyetan, Voke (Universitas Muhammadiyah Sumatera Utara (UMSU), 2026)
The research purpose of this study is to (1) explores students’ levels of nervousness in mathematics among students in secondary school. (2) Investigate the connection among female and male students' mathematics nervousness or anxiety levels. The study design was a correlation. The study sample comprised 300 students which include female and male students in secondary from five schools. The instruments that were utilized for data collection were the questionnaire and the students’ third-term mathematics results. The hypotheses stated to guide the research were two. The multiple regressions, bar chart and pie chart were utilized to analyze collected data. The result from the study indicated that there exist a significant connection between students’ math level of anxiety or nervousness and their mathematics performance. It was revealed that significant difference exist between anxiety in math and gender among students in secondary school. The study’s findings have impacted the insight of students’ levels of anxiety in math and gender disposition among students in secondary school. This research recommends that if performance of students in mathematics is to be enhanced there is demand to control the students anxiety’ levels and also there should be no gender discrimination